Effect of Al substitution on the structural, electric and impedance behavior of cobalt ferrite. (February 2019) - Sathiya Priya, A.; Geetha, D.; Kavitha, N.
Abstract: Cobalt ferrite nanoparticles doped with Al ions, Co1-x Alx Fe2 O4 (x = 0, 0.1, 0.3 and 0.5) were prepared by sol-gel method. An attempt is made to understand if and how the Al substitution affect the structural and electrical properties of cobalt ferrite. The X-ray diffractometer (XRD) analysis confirmed the single phase cubic spinel structure of the nanocrystals. Crystallite size, lattice constant and x-ray density were calculated from the XRD data. A reduction in crystallite size and lattice parameter values were found with increased dopant concentration. Tetrahedral and octahedral hopping lengths and other related parameters were also calculated from the XRD data. The effect of doping on morphological features were monitored using Field emission scanning electron microscope (FESEM) images. The Fourier transform infrared spectrometer (FTIR) spectral analysis confirmed the cubic spinel structure of cobalt ferrite nanoparticles with the occurrence of characteristic absorption bands. Improved values of dielectric constant, low dielectric loss and resistivity were displayed by Al doped ferrite samples. Detailed impedance spectroscopy analysis with the help of Cole-Cole plot explored the capability of the Al doped cobalt ferrite to be suitable for high frequency applications and magnetic memory devices. Highlights: CoFe2 O4 samples was doped with trivalent metal Al using sol-gel method. Crystal structure was determined from the XRD data. The structural morphological changes were monitored. The dielectric parameters were explored. Impedance spectroscopy analysis indicates the material to be suitable for memory device applications.